2010
DOI: 10.2105/ajph.2009.177329
|View full text |Cite
|
Sign up to set email alerts
|

Disparities in Health-Related Quality of Life: A Comparison of Lesbians and Bisexual Women

Abstract: Despite the standard practice of collapsing sexual minority women into a single group, lesbian and bisexual women in this study emerge as distinct groups that merit specific attention. Bisexual women are at elevated risk for poor HRQOL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
124
6
7

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 194 publications
(148 citation statements)
references
References 43 publications
11
124
6
7
Order By: Relevance
“…12 Most of these associations have been identified in LGBT adolescents, although research on sexual minority women has found reduced mental health to be associated with poor health-related quality of life, 44 lack of exercise, 12 and poor general health. 45,12 Mediational models and clinical implications A major goal of this study was to create a path model linking outness through social support and mental health to wellness behavior. Consistent with the hypothesis, in the first model the indirect effects of outness to family and wellness behaviors through social support from family and depression were significant.…”
Section: Discussionmentioning
confidence: 99%
“…12 Most of these associations have been identified in LGBT adolescents, although research on sexual minority women has found reduced mental health to be associated with poor health-related quality of life, 44 lack of exercise, 12 and poor general health. 45,12 Mediational models and clinical implications A major goal of this study was to create a path model linking outness through social support and mental health to wellness behavior. Consistent with the hypothesis, in the first model the indirect effects of outness to family and wellness behaviors through social support from family and depression were significant.…”
Section: Discussionmentioning
confidence: 99%
“…The absence of multivariate models that directly compare bisexual and lesbian women limits our ability to understand the extent to which these two groups actually differ. 9 In two studies that included direct comparisons of bisexual and lesbian women, results were not consistent. In a study using data from the Washington State BRFSS survey, the authors found that even after adjusting for demographic differences, including age and living in poverty, bisexual women had significantly higher odds of frequent mental distress and poor general health than lesbian women.…”
Section: Introductionmentioning
confidence: 97%
“…In a study using data from the Washington State BRFSS survey, the authors found that even after adjusting for demographic differences, including age and living in poverty, bisexual women had significantly higher odds of frequent mental distress and poor general health than lesbian women. 9 Another, more recent study, which relied on a pooled sample of 2010 BRFSS surveys from 10 states, directly compared bisexual and lesbian women on a wide range of health behaviors and outcomes in addition to comparisons to heterosexual women. 13 Once age, race, education and income were controlled, bisexual and lesbian women no longer differed significantly in regard to fair/poor health status, current smoking, HIV risk, or screening behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…There is a small speculative literature on the issues older bisexually-identified people are likely to face when encountering support services (Dworkin, 2006;Rodriguez Rust, 2012;Scherrer, 2017) and some evidence that bisexually-identified women are at increased risk of negative health outcomes across the life course compared to lesbians (Colledge, Hickson, Reid, & Weatherburn, 2015;Fredriksen-Goldsen, Kim, Barkan, Balsam, & Mincer, 2010).…”
Section: Introductionmentioning
confidence: 99%